Students’s Academic Level Stress During Online Learning in Physical Education - Gita Febria Friskawati (STKIP Muhammadiyah Kuningan, 2021)
Changes in online learning, especially in physical education learning, make students feel pressured by the assignments given by the teacher. This study aims to reveal the level of academic stress of students at each level starting from elementary, junior high and high school students when doing online learning of physical education. Survey research was used to uncover this problem. The population consisted of 76 elementary students, 88 junior high school students and 81 high school students scattered in Cimahi City. Taking the sample using convenience sampling technique. The Stress Reaction Checklist (SRCL) instrument was used to measure students' academic stress levels. The calculation uses simple percentage descriptive analysis. The results show that the level of academic stress is different at each level of SD, SMP and SMA in facing online physical education learning. Middle school and high school students have the highest academic stress levels, while elementary students are at medium stress academic levels. There is a need for collaboration between teachers and parents to be able to familiarize students with online learning during the Covid-19 pandemic, although learning with this will not last forever.